Assessment of Knowledge of Autism Spectrum Disorders among Medical Students at the Muhimbili University of Health and Allied Sciences: A Semiquantitative Study (Tanzania Medical Journal, 2022)
IntroductionKnowledge and awareness of Autism is imperative in the diagnosis of Autism. Globally, there is an increase of incidence reported, the situation is Africa is unclear and maybe due to knowledge and awareness gap. The primary care provider in many of our settings is a physician. These obtain their training mainly in the medical school, thus assessing knowledge of medical students would draw attention on the knowledge ga on Autism.MethodologyA cross-sectional, semi-quantitative study among final year medical students at Muhimbili University of health and Allied Sciences. Structured questionnaires were provided to the students who agreed to participate. Autism was divided into 4 domains, and knowledge of each domain was assessed. These domains are 1) communication and speech, 2) social interaction, 3) obsessive and repetitive behaviors and 4) comorbidities.ResultsA total of 136 out of 178 final year medical students participated in this study. The responses were converted to categorical values, where 19 was the maximum score.  The mean score for overall Autism knowledge was 14.48 ± 4.30. The knowledge deficiency in domain 4 (comorbidity) was highest, followed by domain 3 (obsessive behaviour), domain2 (social interaction) and domain 1 (communication).Conclusion and RecommendationIn general, there was a good level of knowledge, and that speech and communication was the most important criteria. This appreciable knowledge level is commendable; however, more effort is needed to improve attitudes and practices.